A comparison of bending fatigue strength of carburized and nitrided gears for industrial applications. (August 2017) - Conrado, Edoardo; Gorla, Carlo; Davoli, Piermaria; Boniardi, Marco
Abstract: An experimental campaign aimed at the assessment and the comparison of the bending fatigue resistance of two case hardened and three nitrited gear steels was performed. Five batches of test gear specimens were produced according to the current industrial practice. Besides standard inspections of gear specimens, accurate X-ray measurements were carried out in order to determine the variations of residual stresses caused by different combinations of steels and thermo-chemical treatments. Single Tooth Bending Fatigue (STBF) tests were conducted to estimate the fatigue limits of the five gear materials, as well as to determine their S-N diagrams. The sensitivity to overload of nitrided steels was investigated by means of additional tests determining the so-called damage line for these materials. The experimental results allowed a comparison of the bending fatigue performances of case carburized and nitrited gears, showing the high competitiveness of the latter. Highlights: A direct comparison of bending fatigue strengths of carburized and nitrided gears Results of STBF tests directly useable in gear calculation methods like ISO 6336 Bending strength of nitrided gears is competitive with that of carburized ones. Overload sensitivity of nitrided gears can be as low as that of carburized ones.